The Political Economy of Natural Resource Use : Lessons for Fisheries Reform - Leal, Donald R. (World Bank, Washington, DC, 2014)
The release of 'Sunken billions: The economic justification for fisheries reform' has drawn renewed attention to the enormous loss of wealth suffered in fisheries each year due to weak fisheries governance and the need for fundamental fisheries reform. Such reform calls for addressing the issues plaguing the world's fisheries, such as persistent overfishing and fleet overcapitalization, and addressing the political economy challenges of developing country-specific pathways of reform. Despite growing evidence of success in selected fisheries, less than two percent of the world's fisheries have actually undergone effective reform because of these challenges. At the same time, it is estimated that the world's fisheries could generate at least fifty billion US dollars per annum and the economic benefits generated could be much higher if management systems were established to enable investment in growing this important economic sector in a sustainable manner. The potential pay-off from economic fisheries reform is not only globally significant for the sector, it is crucial for enhancing economic growth and alleviating poverty in developing countries with significant fisheries assets. This report seeks to move this debate forward by discussing key lessons drawn from reform experience in the wider natural resource sector that might inform successful reform in fisheries.